Konsep Perceraian Di Depan Sidang Pengadilan Perspektif Maqasid Al-Syari’ah Ibnu Asyur - Abdulloh Munir (MAHAKIM Journal of Islamic Family Law, 2019)
The occurrence of divorce, which is increasing from year to year, cannot be separated from the public understanding about divorce, where it can be done anytime and anywhere by the husband. This is a problem that must be resolved, even if it is not suitable to Imam Shafi’i’s opinion, namely the divorce must be applied before a court hearing. This problem must be solved through maqasid sharia. Ibnu Asyur provides solutions; the Qur’an is the greatest and most definite source and contains more than one meaning, the determination and occupation of the problem must be carried out textual and contextual study deeply. The research purpose is to reveal maqasid sharia in the determination of divorce must be applied before the court hearing, especially Ibnu Asyur’s perspective. The method is descriptive qualitative by technique of data reduction, data display and taking conclusion. The results prove the divorce rate from 2015-2018 shows an increase. So according to Ibnu Asyur, Sharia texts are not only studied textually, but are contextual by considering the consequences of divorce and procedures that must be obeyed, and based on human nature in marriage, egalitarian between husband and wife, and freedom of attitude and opinion.